2020
DOI: 10.3390/ijms21113791
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers for Connective Tissue and Basement Membrane Remodeling Are Associated with Vertebral Endplate Bone Marrow Lesions as Seen on MRI (Modic Changes)

Abstract: Vertebral endplate bone marrow lesions, visualized on magnetic resonance imaging (MRI) as Modic changes (MC), are associated with chronic low back pain (cLBP). Since guidelines recommend against routine spinal MRI for cLBP in primary care, MC may be underdiagnosed. Serum biomarkers for MC would allow early diagnosis, inform clinical care decisions, and supplement treatment monitoring. We aimed to discover biomarkers in the blood serum that correlate with MC pathophysiological processes. For this single-site cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…Bone marrow fibrosis is a pathophysiological important mechanism in MC1 and may have diagnostic and clinical relevance (Dudli et al, 2017;Dudli et al, 2020;Modic et al, 1988). The present study showed that BMSCs in MC1 have a profibrotic phenotype compared to BMSCs from control vertebral bone marrow from the same patient.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Bone marrow fibrosis is a pathophysiological important mechanism in MC1 and may have diagnostic and clinical relevance (Dudli et al, 2017;Dudli et al, 2020;Modic et al, 1988). The present study showed that BMSCs in MC1 have a profibrotic phenotype compared to BMSCs from control vertebral bone marrow from the same patient.…”
Section: Discussionsupporting
confidence: 49%
“…Ann Rheum Dis 79: 159; conference abstract; Klingberg et al, 2013]. Importantly, circulating pro-collagen type IV has been reported to be increased in peripheral blood of MC1 patients (Dudli et al, 2020). This shows that increased ECM secretion through fibrotic mechanisms in MC1 has a potential diagnostic value.…”
Section: Pro-fibrotic Ecm Production and Signalling In Mc1 Bmscsmentioning
confidence: 99%
“…15 Biomarkers related to disc resorption and bone marrow fibrosis have been correlated with the presence of MCs. 16 A recent study comparing serum biomarkers between patients with cLBP with MCs and healthy controls reported that several cytokines were suppressed in serum among patients with MC. 17 Some studies report upregulation of cytokines in the disc in MCs, 14 18-20 but no serum biomarker is established for MCs.…”
Section: Key Messagesmentioning
confidence: 99%
“…All analyses were done using SPSS V.27, STATA V. 16 and the R programming language (http://www. r-project.…”
Section: Statisticsmentioning
confidence: 99%
“…Изучались сывороточные биомаркеры повреждения соединительной ткани и ремоделирования основной мембраны, ассоциированные с повреждениями концевой пластины костного мозга, видимыми на МРТ (изменения по Modic) [29]. В исследовании участвовали 38 пациентов с хронической болью в нижней части спины и 16 здоровых добровольцев.…”
Section: биомаркеры хронической болиunclassified